2017
DOI: 10.1007/s00299-017-2170-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of adventitious shoot regeneration in roses by employing genome-wide association studies

Abstract: We analysed the capacity to regenerate adventitious shoots in 96 rose genotypes and found 88 SNP markers associated with QTLs, some of which are derived from candidate genes for shoot regeneration. In an association panel of 96 rose genotypes previously analysed for petal colour, we conducted a genome-wide association study on the capacity of leaf petioles for direct shoot regeneration. Shoot regeneration rate and shoot ratio (number of shoots/total number of explants) were used as phenotypic descriptors for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…2 ). These maps have enabled subsequent quantitative trait locus (QTL) mapping studies 10 and genome-wide association analyses 11,12 in tetraploid rose, helping to identify regions of the genome that are statistically correlated with traits of interest. As the genomes and most of the resources are publicly available, rose genomics is far more accessible than ever before.…”
Section: Introductionmentioning
confidence: 99%
“…2 ). These maps have enabled subsequent quantitative trait locus (QTL) mapping studies 10 and genome-wide association analyses 11,12 in tetraploid rose, helping to identify regions of the genome that are statistically correlated with traits of interest. As the genomes and most of the resources are publicly available, rose genomics is far more accessible than ever before.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a GWAS on embryonic callus regeneration in maize showed that only 15 out of 63 QTNs were retained in multiple environments and highlighted WUSCHEL-RELATED HOMEOBOX 2 (WOX2) , although other candidates are distinct from ours 37 . Most QTGs we identified are also new compared to association studies on adventitious shoot regeneration in roses 38 , callus formation in poplar 39 and rice 40 and in vitro regeneration of cucumber 41 and tomato 42 . However, these studies do report similar functional classes of candidates (e.g., embryogenesis and meristem genes, reprogramming factors, hormone-related proteins, receptor-like kinases, and TFs from the LBD, ERF, MYB, and WOX families) 37 40 and in cases where multiple traits, protocols or techniques are evaluated, overlap between them is limited 37 , 38 , suggesting that the difference in experimental systems could be part of the cause.…”
Section: Discussionmentioning
confidence: 92%
“…Most QTGs we identified are also new compared to association studies on adventitious shoot regeneration in roses 38 , callus formation in poplar 39 and rice 40 and in vitro regeneration of cucumber 41 and tomato 42 . However, these studies do report similar functional classes of candidates (e.g., embryogenesis and meristem genes, reprogramming factors, hormone-related proteins, receptor-like kinases, and TFs from the LBD, ERF, MYB, and WOX families) 37 40 and in cases where multiple traits, protocols or techniques are evaluated, overlap between them is limited 37 , 38 , suggesting that the difference in experimental systems could be part of the cause. Notably, several established SAM genes, epigenetic factors and cell cycle regulators (e.g., STM, CUCs, ESRs, PLTs, WIND1, MET1, and CYCD3 13 ) were not detected in our assay, which might be due to a lack of functional sequence variation at these loci in the tested population 43 .…”
Section: Discussionmentioning
confidence: 92%
“…This new reference sequence is an important tool to decipher the genetic basis of ornamental traits such as blooming (including continuous flowering, flower development and number of petals), prickle density on the stem and self-incompatibility. We studied the genetic determinism ( i ) in two F1 progenies (151 individuals, obtained from a cross between R. chinensis ‘Old Blush’ and a hybrid of R. wichurana (OW) and 174 individuals obtained from a cross between ‘Yesterday’ and R. wichurana (YW)) and ( ii ) in a panel of 96 rose cultivars originating from the 19 th to the 21 st century [30, 31]. Our data demonstrate that important loci controlling continuous flowering, double flower morphology, self-incompatibility and prickle density were predominantly localised on a genomic region on Chromosome 3 (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%